Poddubniy I., Kubich V., Korobochka A. Wear resistance of the strengthened facet of the valve and parame-tres of contact interaction of elements tribointerface "a valve facet - a saddle". - Поддубный, И.Н.; Кубич, В.И.; Коробочка, А.Н. (Problems of Tribology, 2014)
There are definition of a way of a friction for interface "a valve facet – a saddle" taking into account vertical moving of contact on a spiral is offered at closing of the valve and its horizontal rotation on a circle at opening at the expense of work of the mechanism of compulsory rotation for n quantity of cycles for an operating time in the work. The technology of superficial hardening of details of mechanisms and internal combustion engine systems is developed. Mehano-geometrical characteristics of a blanket of valves’ facets are defined. As a result of data processing on loading parametres, to the geometrical sizes of valves, control weighing after each time indicator of tests, are defined settlement by linear wear facets that has allowed to calculate intensity of wear process and their wear resistance. The received system of the equations solved Kramer’s method. Experimental data of results of tests of the strengthened facet have allowed to make of them the dimensionless generalised complexes and to approximate their influence on wear resistance regress dependence. The mathematical description of wear resistance of the strengthened surface of a facet of the valve of an internal combustion engine from parametres of contact interaction taking into account its wear process on the way of a friction integrated by two movings is developed. There are spatial diagrammes of wear resistance of facets of the valve after tribotehnical tests are constructed.